2019
DOI: 10.17559/tv-20170924230143
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Control in the Process of Low-Rigidity Elastic Deformable Shafts Turning

Abstract: The paper focuses on the problem of control of accuracy of forming elastic-deformable shafts with low rigidity. In particular, results of analysis of basic factors affecting the accuracy of machining of low-rigidity shafts such as the stiffness of the technological system, geometry of cutting tool, lathe temperature, degree of cutting tool wear, cutting tool strength, lubrication-cooling fluid and machining parameters are presented. Moreover, the performed analysis encompassed the effect of stiffness of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Based on the analysis of many industrial products it can be concluded that one half of all machine parts are rotational parts: shafts (over 40%), discs, sleeves, thin wall cylinders, rings, etc. [57].…”
Section: Subject and Research Methodsmentioning
confidence: 99%
“…Based on the analysis of many industrial products it can be concluded that one half of all machine parts are rotational parts: shafts (over 40%), discs, sleeves, thin wall cylinders, rings, etc. [57].…”
Section: Subject and Research Methodsmentioning
confidence: 99%